2019
DOI: 10.1088/1748-9326/ab2cc0
|View full text |Cite
|
Sign up to set email alerts
|

The evolution, propagation, and spread of flash drought in the Central United States during 2012

Abstract: During 2012, flash drought developed and subsequently expanded across large areas of the Central United States (US) with severe impacts to overall water resources and warm-season agricultural production. Recent efforts have yielded a methodology to detect and quantify flash drought occurrence and rate of intensification from climatological datasets via the standardized evaporative stress ratio (SESR). This study utilizes the North American Regional Reanalysis and applied the SESR methodology to quantify the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 42 publications
2
71
0
2
Order By: Relevance
“…Past studies (e.g., Fitzjarrald and Lala 1989;Wingo and Knupp 2015) of the AET in other locations have also suggested that this process may be the primary cause behind the increase in q y observed during the hours prior to sunset. Combined with past work, our results broadly suggest that evapotranspiration-driven AET q y jumps may be a part of the coupling known that exists between the land surface and atmosphere in the SGP (Basara and Crawford 2002).…”
Section: B Environmental Controls On the Presunset Q Y Maximumsupporting
confidence: 83%
See 2 more Smart Citations
“…Past studies (e.g., Fitzjarrald and Lala 1989;Wingo and Knupp 2015) of the AET in other locations have also suggested that this process may be the primary cause behind the increase in q y observed during the hours prior to sunset. Combined with past work, our results broadly suggest that evapotranspiration-driven AET q y jumps may be a part of the coupling known that exists between the land surface and atmosphere in the SGP (Basara and Crawford 2002).…”
Section: B Environmental Controls On the Presunset Q Y Maximumsupporting
confidence: 83%
“…These three regions represent three distinct land surface types that undergo seasonal shifts in land surface properties each year. These groups span across a climatological west-east soil moisture gradient that has been the subject of several land-atmosphere coupling studies in the SGP (Illston et al 2004;Ford et al 2015a,b,c;Basara and Christian 2018;Wakefield et al 2019;Basara et al 2019). In comparison with the other two groups, the W-WWB region has the highest elevation…”
Section: Aet Extrema Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, individual case studies have primarily been used to examine the characteristics of rapid onset drought. For example, Otkin et al (2016) and Basara et al (2019) explored the temporal and spatial evolution of the 2012 flash drought event across the central US. Hunt et al (2014) investigated a flash drought event that occurred in Mead, Nebraska in 2003 by comparing soil water, evapotranspiration, and gross primary productivity to two drought indices and its effect on dryland crop yields.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid onset of drought leaves limited time for preparation and drought mitigation, causing devastating impacts due to insufficient early warning [ 5 , 6 ]. The increasing frequency of flash drought in a warming climate [ 4 , 7 ] presents a higher risk on vegetation health, food security, and ecosystem and environmental sustainability [ 8 , 9 ]. Extreme drought events could dampen carbon uptake and accelerate atmospheric carbon dioxide concentrations [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%